Penampilan 10 Kandidat Jagung Hibrida Berdaya Hasil Tinggi dan Toleran terhadap Kekeringan - Ramlan, Ach Rofiqi; Amzeri, Achmad; Chan, Caroline; Suhartono, Suhartono; Umam, Ahmad Syaiful (Universitas Trunojoyo Madura, 2025)
One way to increase maize productivity in dry land is to develop superior maize varieties with high production, early maturity, and resistance to drought stress. The study aims to evaluate the characteristics of 10 hybrid maize candidates with high production, early maturity and resistance to drought stress. The research used a Randomized Complete Block Design (RCBD) with 13 genotypes (10 hybrid maize candidates, three comparison varieties (Jakaring, Pioneer-X, and Bisi-X)) as treatments. It was repeated three times, so that there were 39 experimental units. Drought stress using the CYMMYT method, namely drought stress, is carried out when the plants are 50 DAP until harvest, but providing irrigation with field capacity at 0 to 40 DAP with an interval of every 10 days. The observation parameters in this study were plant height, number of leaves, leaf length, leaf area, ear height, days of 50% tasseling, days to 50% silking, harvest age, number of kernel rows, weight of cob with husk, ear length, ear diameter, kernel width, kernel length, kernel thickness, kernel diameter, 1000-kernel weight, and production per hectare. The results of the study showed that the thirteen tested characters showed a very significant effect of the treatment, namely plant height, number of leaves, leaf length, leaf area, ear height, days of 50% tasseling, days to 50% silking, harvest age, number of kernel rows, weight of cob with husk, ear length, kernel width, and 1000-kernel weight. Four characters showed a significant effect of treatment: kernel length, kernel thickness, kernel diameter, and production per hectare. The ear diameter character did not show any significant differences between treatments. The broad heritability values for all tested characters for the 13 genotypes ranged from 49.90 to 97.90. Production per hectare was positively correlated with ear length (0.79**), ear diameter (0.37*), and kernel thickness (0.59**). Furthermore, the production character per hectare is negatively correlated with harvest age (-0.49**) and kernel length (-0.38*). G1, G2, G3, and G6 are the hybrid maize candidates selected for the release of hybrid varieties with high production and early maturity.